1999
DOI: 10.1203/00006450-199907000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Limited Proteolysis of the IGF Binding Protein-2 (IGFBP-2) by a Specific Serine Protease Activity in Early Breast Milk

Abstract: IGF in milk possibly promote maturation of the gastrointestinal tract in newborns. We studied the composition of milk samples derived from 99 healthy women at regular intervals during a period beginning 3 d and ending 6 mo after birth. The concentrations measured by RIA on d 3 were 10.7+/-0.4 ng/mL for IGF-II, 1.9+/-0.1 ng/mL for IGF-I, 100+/-5 ng/mL for IGF binding protein-3 (IGFBP-3), and 2163+/-108 ng/mL for IGFBP-2. All factor concentrations decreased by up to 70% in the course of the 6 mo. The most striki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 18 publications
5
27
1
Order By: Relevance
“…Partial hydrolysis of milk proteins by co-secreted proteases would release peptide fragments including di-and tripeptides, and those may be reabsorbed by PEPT2 into epithelial cells. In addition, specific hydrolysis of biologically active proteins, such as binding proteins for insulin-like growth factors in human milk, has been reported (14) that also would release short-chain peptides. These peptides either could be submitted to hydrolysis by surface-bound aminopeptidases (5, 13) to yield free amino acids or may be transported in intact form into the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Partial hydrolysis of milk proteins by co-secreted proteases would release peptide fragments including di-and tripeptides, and those may be reabsorbed by PEPT2 into epithelial cells. In addition, specific hydrolysis of biologically active proteins, such as binding proteins for insulin-like growth factors in human milk, has been reported (14) that also would release short-chain peptides. These peptides either could be submitted to hydrolysis by surface-bound aminopeptidases (5, 13) to yield free amino acids or may be transported in intact form into the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the IGF measurement interfering with the IGFBPs present in breast milk, we used IGF-1 and IGF-2 assays that made use of the principle of excess IGF-2 or IGF-1, respectively. This is a standard approach to make IGFBP assays more reliable (7,8). The sensitivity of all assays was Ͻ0.2 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The RIAs were competitive binding assays for serum utilizing 125 I-labeled IGF-1, IGF-2, IGFBP-2, or IGFBP-3. Using human milk whey as the assay matrix instead of serum, the RIAs had been evaluated previously for linearity, precision, and recovery (7,8, and unpublished data). The precision of measurement of IGF-I, IGF-II, IGFBP-2, and IGFBP-3 were 7.5, 8.9, 7.8, and 9.2% coefficient of variation (CV), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…IGFBP-2, the second most frequent IGFBP in the human circulation, is involved in many physiological and pathological conditions and processes: IGFBP-2 is highly expressed during the perinatal period (Blum et al 1993, Lindenbergh-Kortleve et al 1997, while in adults the highest concentrations of IGFBP-2 are found in cerebrospinal fluid (Binoux et al 1991, Arnold et al 1999), mother's milk (Elmlinger et al 1999) and seminal plasma (Rosenfeld et al 1990). IGFBP-2 is also often highly expressed in malignant tumor cells but decreases upon remission (Muller et al 1994, Elmlinger et al 1996, Hoeflich et al 2000, Elmlinger et al 2001, Moore et al 2003, Ranke et al 2003.…”
Section: Introductionmentioning
confidence: 99%